2020
DOI: 10.1371/journal.pone.0233623
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between spinal schwannomas and meningiomas using MRI: A focus on cystic change

Abstract: ObjectivesTo retrospectively determine the diagnostic ability of MRI in differentiating between intradural extramedullary spinal schwannomas and meningiomas. MethodsA total of 199 patients with spinal intradural extramedullary tumors who underwent preoperative contrast-enhanced MRI between January 2012 and December 2018 were included in this study. Two radiologists independently analyzed the presence of cystic change, dural tail sign, and neural foraminal extension. Clinical and MRI features between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…In this study, the tumor size of schwannomas (median 11.9; 95% CI: 7.7-59.6) was significantly larger than that of meningiomas (median 9.73; 95% CI: 6.5-23.9). The study by Lee et al [10] also reported a similar result. Additionally, our study found that men were significantly more likely to be diagnosed with schwannoma than meningioma, and schwannomas were significantly more likely to be located in the cervical and lumbar spine and in a lateral position on the horizontal axis.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In this study, the tumor size of schwannomas (median 11.9; 95% CI: 7.7-59.6) was significantly larger than that of meningiomas (median 9.73; 95% CI: 6.5-23.9). The study by Lee et al [10] also reported a similar result. Additionally, our study found that men were significantly more likely to be diagnosed with schwannoma than meningioma, and schwannomas were significantly more likely to be located in the cervical and lumbar spine and in a lateral position on the horizontal axis.…”
Section: Discussionsupporting
confidence: 54%
“…Schwannomas presented with a heterogeneously hyperintense signal on T2W in the study reported by Verdelhan et al 11 . The studies by Iwata et al 14 , Zhai et al 2 , and Lee et al 10 also reported significantly increased fluid signals on T2W in schwannomas are significantly higher than those of meningiomas. The fluid signals are indicated by signal intensity equal to that of the cerebrospinal fluid, exhibiting hypointense on T1WI, hyperintense on T2WI and show no enhancement after contrast administration.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…If a calcified area is included, the signal may change to low. [3], [7] Management of spinal IDEM tumors is tumor resection surgery but biopsy is the only method to definitively confirm diagnosis through tumor resection surgery. [8], [9], [10] The pathognomonic histologic feature of a meningioma is spherical formations of meningothelial cells, called whorls, which eventually mineralize into psammoma bodies.…”
Section: Introductionmentioning
confidence: 99%